Penguatan Kelembagaan Sekolah Inklusi di Kabupaten Banyumas: Bebas Tiga Dosa Besar Pendidikan - Chamadi, Muhamad Riza; Tyas Retno Wulan; Tri Wuryaningsih; Tri Rini Widyastuti (Solidaritas: Jurnal Pengabdian, 2025)
Education is a basic right of every citizen guaranteed by various national regulations. However, in prac-tice, inclu-sive schools in Indonesia still face various challenges, such as limited teacher competency in handling Children with Special Needs (ABK), minimal facilities and infrastructure, weak institutional systems, and social stigma from the community. This condition has implications for the emergence of the phenomenon of "three major sins of education" including sexual violence, bullying, and intolerance. Based on a 2024 study of 408 teachers in Banyumas Regency, it was found that bullying cases dominat-ed with a percentage of 87 percent, followed by in-tolerance at 5 percent, and sexual violence at 0.28 percent. Responding to this problem, the community service team held a workshop on strengthening inclusive school institutions with the aim of increasing the capacity, awareness, and practical skills of education stakeholders. This activity was carried out through the presentation of conceptual materials, technical training, and participatory discussion forums involving teachers from differ-ent inclusive schools. The results of the activity showed an increase in teachers' understanding of the concept of in-clusive education, violence prevention strategies, and skills in handling ABK adaptively. In addition, this pro-gram can also be used as a stepping stone in strengthening a safe and discrimination-free inclusive education eco-system, as well as being a preventive strategy in suppressing cases of the three major educational sins in the school environment.